Pengaruh Board Commisioners Size dan Company Size Terhadap Social Disclosure - Mar’ati, Fudji Sri; Darsono, Darsono (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this research is to find out whether board commissioners size and company size have an effect on social disclosure. The population of this study are companies listed on LQ45 on IDX for the 2019-2021 period. This research data uses secondary data in the form of financial reports from IDX. The analysis tool used is SEM-PLS (Structural Equation Modeling based on Partial Least Square). The test results show that board commissioners size has a positive and significant effect on social disclosure. Likewise, company size has a positive and significant influence on social disclosure.